2019
DOI: 10.1002/prp2.463
|View full text |Cite
|
Sign up to set email alerts
|

A novel soluble guanylate cyclase activator with reduced risk of hypotension by short‐acting vasodilation

Abstract: Cinaciguat, a soluble guanylate cyclase ( sGC ) activator, was under clinical development for use in acute decompensated heart failure ( ADHF ), but was discontinued due to occurrence of hypotension. We hypothesized that short‐term activation of sGC in ADHF patients would exert a vasodilative effect without hypotension irrespective of disease state, using a novel short‐acting sGC activator, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…NASH) are warranted, especially when using combinations of sGC agonists and PDE-5 inhibitors 33 or promising second-generation sGC activators with an improved pharmacokinetic profile. 34 In conclusion, our study supports the therapeutic potential of the sGC stimulator RIO and the PDE-5 inhibitor TADA for cirrhotic PHT. Both drugs decreased PP by reducing IHVR via the promotion of sinusoidal vasodilation and a reduction of liver fibrogenesis.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…NASH) are warranted, especially when using combinations of sGC agonists and PDE-5 inhibitors 33 or promising second-generation sGC activators with an improved pharmacokinetic profile. 34 In conclusion, our study supports the therapeutic potential of the sGC stimulator RIO and the PDE-5 inhibitor TADA for cirrhotic PHT. Both drugs decreased PP by reducing IHVR via the promotion of sinusoidal vasodilation and a reduction of liver fibrogenesis.…”
Section: Discussionsupporting
confidence: 74%
“…Further experimental studies in other chronic liver disease settings (i.e. NASH) are warranted, especially when using combinations of sGC agonists and PDE‐5 inhibitors 33 or promising second‐generation sGC activators with an improved pharmacokinetic profile 34 …”
Section: Discussionmentioning
confidence: 99%
“…Our results therefore indicate the need of caution with drugs that chronically activate the NO-sGC-PRKG signaling pathway, since they may be detrimental to aortic homeostasis. These drugs include advanced sGC stimulators such as Vericiguat (BAY 1021189) and Riociguat (BAY 63-2521), the latter having received FDA approval for pulmonary hypertension and heart failure 50,51 , as well as novel short-acting sGC activators that lack hypotensive side effects, such as TY-55002, a candidate for the treatment of patients with acute decompensated heart failure 52 . Seemingly in conflict with our results, increased NO production by constitutively active Nos3 has been reported to exert a beneficial effect on the aorta in MFS mice 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, an sGC agonist, riociguat, is approved by the FDA for treating pulmonary hypertension. It has shown a favorable safety profile and is well tolerated, with hypotension and syncope as the most frequent side effect 53 . A randomized, controlled, phase IIb trial of cinaciguat use for acute heart failure syndromes showed the short‐term use of intravenous cinaciguat caused frequent hypotension without beneficial effects on respiratory and cardiac index 54 .…”
Section: Sgc and Bonementioning
confidence: 99%